Endoscopic and clinicopathological features of segmental colitis associated with diverticulosis - Kazuhiko Obata; Kan Uchiyama; Ryuzo Murai (DEN Open)
Abstract Objectives Segmental colitis associated with diverticulosis (SCAD) has close endoscopic and pathological similarities to ulcerative colitis (UC) and Crohn's disease. Clinical data on SCAD are limited in Japan. We examined the endoscopic and clinicopathological features of patients with SCAD. Methods This single‐center retrospective study included 13 patients with SCAD between 2012 and 2022. Endoscopic findings were categorized as follows: type A (swollen red patches 5–10 mm at the top of mucosal folds), mild and moderate type B (mild‐to‐moderate UC‐like findings), type C (aphthous ulcers resembling Crohn's disease), and type D (severe UC‐like findings). Results Overall, six, five, and two patients were diagnosed with type A, mild type B, and moderate type B disease, respectively. Among the type A cases, two spontaneously progressed to moderate type B and one escalated to type D, necessitating an emergency sigmoidectomy owing to perforation peritonitis, despite repeated antibiotic treatments. Histopathologically, diffuse neutrophil and lymphocyte infiltration with cryptitis were noted in all type A cases, whereas UC‐like alterations were observed in type B and D cases. Seven type B cases were treated with oral 5‐aminosalicylic acid and/or salazosulfapyridine. Clinical remission was achieved in three mild type B cases and one moderate type B case, while clinical relapse and remission were noted in three moderate type B cases. No anti‐inflammatory treatment was required in three type A and two mild type B cases. Conclusions Aggressive anti‐inflammatory treatment should be considered for SCAD with UC‐like findings due to the potential risk of severe ulceration, stenosis, and/or perforation.